A secure framework for vehicle maintenance service using blockchain - Mohd Ab Razak, Nur Shuhadah; Mansor, Hafizah; Sharmin, Shaila (Association for Computing Machinery, 2023)
Automotive technology is soaring and has reached an advanced phase. Despite their benefits, these advancements may expose vehicles to additional threats, particularly in terms of security and data management. This paper focuses on the application of vehicle maintenance services, specifically on maintenance history records. Currently, handling maintenance services history is a manual process which may give rise to inaccuracy and unavailability. Moreover, consumers rarely have access to these records unless they keep hardcopy-based records for the maintenance services performed on their cars. Those issues bring another concern that there are no reliable platforms or legitimate sources to retrieve the history of maintenance service records. Thus, the objectives of this paper are to identify the relevant stakeholders and determine their roles in the vehicle maintenance services industry. Hence, the list and details of stakeholder is considered and applied accordingly in the design of a secure framework that provides the necessary security goals for the maintenance services records. The proposed framework implements blockchain technology based on two use cases which are the Framework for Scheduled Maintenance Service and the Framework of Repair Maintenance Service. The use of this framework by the stakeholders in the automotive ecosystem would ensure the implementation of the required security goals in the maintenance services application. The method that is being used in this research is literature reviews which is to find out the best approach to be applied in the framework as well as listing out the stakeholder involved and their roles. Next, a secure framework has been designed to produce secure vehicle maintenance records that covers the security requirements needed. As a result, the contributions of this work are the list of stakeholders and their roles, security requirements that need to be taken into consideration and a secure framework for vehicle maintenance records involving all stakeholders.